2018
DOI: 10.1111/jiec.12778
|View full text |Cite
|
Sign up to set email alerts
|

Urban Metabolism of Intermediate Cities: The Material Flow Analysis, Hinterlands and the Logistics‐Hub Function of Rennes and Le Mans (France)

Abstract: Summary Although urban metabolism has been a subject of renewed interest for some years, the related studies remain fragmented throughout the world. Most of them concern major cities (megacities and/or national capitals) and, more rarely, intermediate, medium‐sized or small cities. However, urbanization trends show that together with the metropolization process, another one is characterized by the proliferation of intermediate cities. We have studied the metabolism of two French intermediate cities for the yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 25 publications
0
20
0
4
Order By: Relevance
“…The objective of this work is to comprehensively address outsourcing issues in order to enhance their integration in urban metabolism studies. It contributes to the growing efforts in urban metabolism research to develop spatial approaches for flows' accounting, with the ultimate goal of better contextualizing urban policies' consequences at different scales (Athanassiadis et al, 2015;Bahers et al, 2018;Guibrunet et al, 2016;Huang et al, 2018). In this paper, a multiscale extended territory-based approach was developed, looking at both the dependency on external hinterlands and the generation of external hidden flows (embodied consumption and energy losses) due the city's demand in resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of this work is to comprehensively address outsourcing issues in order to enhance their integration in urban metabolism studies. It contributes to the growing efforts in urban metabolism research to develop spatial approaches for flows' accounting, with the ultimate goal of better contextualizing urban policies' consequences at different scales (Athanassiadis et al, 2015;Bahers et al, 2018;Guibrunet et al, 2016;Huang et al, 2018). In this paper, a multiscale extended territory-based approach was developed, looking at both the dependency on external hinterlands and the generation of external hidden flows (embodied consumption and energy losses) due the city's demand in resources.…”
Section: Discussionmentioning
confidence: 99%
“…Material and energy flow analysis has been applied to many cities and metropolitan areas over the last two decades. Studies have been conducted on large cities, such as Paris (Barles, 2009;Kim and Barles, 2012), Stockholm (Rosado et al, 2016) and Singapore (Schulz, 2007), intermediate cities like Rennes and Le Mans in France (Bahers et al, 2018) and metropolitan areas like the Brussels Capital Region (Athanassiadis et al, 2016) and Los Angeles county (Ngo and Pataki, 2008). The metabolic profiles of several port-cities have also been analyzed including Amsterdam (Voskamp et al, 2017), Hamburg (Hammer et al, 2003), Gothenburg (Rosado et al, 2016) and Lisbon (Rosado et al, 2014).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…We chose MFA to assess the trajectory of intra and extra-island flows by quantifying them, but also by spatializing them. This method also makes it possible to characterize stocks and material consumption by measuring flows of materials and energy entering the island, which are transformed and disposed of [45][46][47]. In addition, previous research has demonstrated the value of using MFA to understand resources nexus [21,48].…”
Section: At the Level Of The Island Flowsmentioning
confidence: 99%
“…), ce qui est très peu abordé par ce registre d'études. En effet, l'AFM nécessite, dans la plupart des cas, un croisement de nombreuses bases de données (Bahers, Barles, Durand, 2019). Comment établir une méthode de quantification des flux de matière et d'énergie lorsqu'une majorité des activités économiques est exercée par des acteurs informels ?…”
Section: Introductionunclassified